DETERMINASI KEPUTUSAN PEMBELIAN BERDASARKAN BRAND IMAGE DAN BRAND TRUST PADA PRODUK IPHONE DI KOTA MATARAM - Putri, Ni Nyoman Ngurah Destri; Sudarma, I Made; Jelantik, Sayu Kadek (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Consumer purchasing decisions are influenced by brand image and trust. The simultaneous influence of brand image and brand trust on iPhone product purchases in Mataram City was studied in this study using quantitative methodology. Data collection methods with observation, documentation, and questionnaire distribution. The sampling used was the accidental sampling technique using certain criteria in sampling with the calculation of the Lemeshow formula totaling 96 respondents. The analysis method used was multiple linear regression. The results of the study obtained in this study were that brand image did not have a partial effect on purchasing decisions with a small t count from the t table, namely 1.759 <1.985 and a significance value greater than 0.05, namely 0.082. Brand trust had a partial effect on purchasing decisions with a t count greater than the t table, namely 6.465> 1.985 and a significance value less than 0.05, namely 0.000. Brand image and brand trust simultaneously influence purchasing decisions with a calculated F value greater than the F table, which is 49.219> 3.09 and a significance value smaller than 0.05, which is 0.000. The determination coefficient test obtained in this study was 0.504 or 50.4%. This means that brand image and brand trust have a 50.4% influence on purchasing decisions. So it is concluded that brand image has no influence, because there are other factors that influence consumers in making purchasing decisions, namely brand trust.